Statins decrease neuroinflammation and prevent cognitive impairment after cerebral malaria. - Patricia A Reis; Vanessa Estato; Tathiany I da Silva; Joana C d'Avila; Luciana D Siqueira; Edson F Assis; Patricia T Bozza; Fernando A Bozza; Eduardo V Tibiriça; Guy A Zimmerman; Hugo C Castro-Faria-Neto (PLoS Pathogens, 2012)
Cerebral malaria (CM) is the most severe manifestation of Plasmodium falciparum infection in children and non-immune adults. Previous work has documented a persistent cognitive impairment in children who survive an episode of CM that is mimicked in animal models of the disease. Potential therapeutic interventions for this complication have not been investigated, and are urgently needed. HMG-CoA reductase inhibitors (statins) are widely prescribed for cardiovascular diseases. In addition to their effects on the inhibition of cholesterol synthesis, statins have pleiotropic immunomodulatory activities. Here we tested if statins would prevent cognitive impairment in a murine model of cerebral malaria. Six days after infection with Plasmodium berghei ANKA (PbA) mice displayed clear signs of CM and were treated with chloroquine, or chloroquine and lovastatin. Intravital examination of pial vessels of infected animals demonstrated a decrease in functional capillary density and an increase in rolling and adhesion of leukocytes to inflamed endothelium that were reversed by treatment with lovastatin. In addition, oedema, ICAM-1, and CD11b mRNA levels were reduced in lovastatin-treated PbA-infected mice brains. Moreover, HMOX-1 mRNA levels are enhanced in lovastatin-treated healthy and infected brains. Oxidative stress and key inflammatory chemokines and cytokines were reduced to non-infected control levels in animals treated with lovastatin. Fifteen days post-infection cognitive dysfunction was detected by a battery of cognition tests in animals rescued from CM by chloroquine treatment. In contrast, it was absent in animals treated with lovastatin and chloroquine. The outcome was similar in experimental bacterial sepsis, suggesting that statins have neuroprotective effects in severe infectious syndromes in addition to CM. Statin treatment prevents neuroinflammation and blood brain barrier dysfunction in experimental CM and related conditions that are associated with cognitive sequelae, and may be a valuable adjuvant therapeutic agent for prevention of cognitive impairment in patients surviving an episode of CM.